Endocrine Regulation of Maturation and Sex Change in Groupers - Kiyoshi Soyano; Takafumi Amagai; Tomofumi Yamaguchi; Yuji Mushirobira; Wen-Gang Xu; Nhan Thành Phạm; Ryosuke Murata (Cells, 2022)
Groupers are widely distributed in tropical and subtropical areas worldwide, are key species to coastal ecosystems, and valuable fishery targets. To facilitate artificial seed production technology for grouper aquaculture, the mechanisms of reproduction and gonad development are being elucidated for these important species. In addition, since groupers are sexually dimorphic fish with female-first maturity (protogynous hermaphrodite fish), research is being conducted to clarify the ecological mechanism of sex change and their reproductive physiology, focusing on the endocrine system. In recent years, research on groupers has also been conducted to understand changes in the coastal environment caused by ocean warming and man-made chemicals. However, due to difficulties associated with conducting research using wild populations for breeding experiments, knowledge of the physiology and ecology of these fish is lacking, especially their reproductive physiology. In this review, we present information on the reproductive physiology and endocrinology of groupers obtained to date, together with the characteristics of their life history.